ChemInform Abstract: High‐Pressure Synthesis and Characterization of New Actinide Borates, AnB4O8 (An: Th, U). Issue 7 (18th February 2014) - Hinteregger, Ernst; Hofer, Thomas S.; Heymann, Gunter; Perfler, Lukas; Kraus, Florian; Huppertz, Hubert
Abstract ThB4O8 and UB4O8 are synthesized from the corresponding metal oxides and B2O3 at 5.5 and 10.5 GPa, respectively (multianvil Walker‐type apparatus, 1100 °C, 10 min).